EXPLORING SCAFFOLDING APPROACH TO TEACH ENGLISH IN HIGHER EDUCATION - Evenddy, Sutrisno Sadji; Gailea, Nurhaeda; Syafrizal, Syafrizal (Universitas Tanjungpura, 2024)
The purpose of this study is to investigate the effectiveness of scaffolding strategies in facilitating English language learning and proficiency among students in higher education settings. This study employs a comprehensive literature review method to systematically examine and synthesize existing scholarly works related to the application of scaffolds in teaching English. The literature review also scrutinizes challenges and considerations in implementing scaffolding, providing a foundation for the identification of gaps in current research and areas that require further exploration. The study explores pedagogical strategies, assess the integration of technology, delve into collaborative learning environments, and investigate real-world applications of the scaffolding in language education.